Scenario planning : the future of Bosch Projects as seen through the sugar industry lens. - Madiba, Mhlengi Arthur. (2012)
This research explores the application of scenario planning to an engineering and project management consulting company based in Durban, South Africa. Scenario planning is used to formulate possible scenarios that this company' main client industry/ market may face in the next ten years. This application provides an opportunity for the consultancy to test if it is necessary for it to start pursuing other markets in order to minimize risk associated with its core market and mostly it prepares the consultancy for opportunities and threats that may exist but is currently not aware of. The research takes the following approach and sequence: . Introduction: The section gives a background into Bosch projects and the sugar industry. It also places me in the context of the research. . Literature Survey: In this section I review general thinking around strategy formulation, organizational learning, metaphors and system thinking. I also draw a link amongst these areas of learning. . Research Methodology: This section presents the methodology I followed in conducting the research. The research started with conversations with research participants followed up with questionnaires. The questionnaires were supplemented with one- on- one interviews with the participants in order gain more clarity on their responses. Scenario planning exercises were conducted with Bosch Projects' management team and the sugar industry participants. Three scenarios were developed with BP and another three with the sugar industry. I developed two additional scenarios for each group for my own interest. . Results Analysis: In this section I present the results of the research process. I start off by discussing the environmental scan analysis which describes the external environment within which the sugar industry operates. This discussion is informed by the results of the interviews with the participants. The general consensus was that the industry is faced with many positive possibilities. It also became clear that the industry is not taking full advantage of opportunities already available to them. In the same section I present the scenarios developed which highlight the challenges faced by the country and how they could affect the industry in the long term. . Conclusion: I then close off the research by making a conclusion that Bosch Projects has a positive future when viewed through the sugar industry lens irrespective of which uncertainties materialize but there are key issues which the company must address in order to be prepared for any of the eventualities. . Value: This research eventually revealed itself to be about learning to effectively lead a scenario planning session and what pitfalls to look out for when creating storylines. There is great value for people interested in finding progressive and well informed ways for strategy formulation. This scenario planning research is grounded on the concepts of a learning organization and systems thinking as the core drivers === Thesis (M.Com.)-University of KwaZulu-Natal, Westville, 2010.